MANIFESTASI MASALAH PADA REMAJA LAKI-LAKI DAN PEREMPUAN YANG TELAH SEMBUH DARI KUSTA - Franciscus Adi Prasetyo; Nur Dyah Gianawati; Kusuma Wulandari; Wahyuni Mayangsari (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2022)
Signs in the form of spots caused by leprosy are a characteristic that in general can affect adolescent boys and girls who experience it to feel anxiety because they are worried that they will receive unpleasant treatment from others due to stigma and discrimination. Therefore, the purpose of this study is to describe the manifestation of the problem of leprosy in adolescent boys and girls who have recovered from leprosy. This study used descriptive qualitative research methods, which was conducted in Indramayu Regency by interviewing three teenage boys and two teenage girls who were selected based on purposive sampling technique. Some important results obtained through this research are: a) changes in self-concept from before leprosy where the teenagers felt themselves as attractive, to a teenager who tends to have a negative selfconcept; b) relations with the opposite sex, with a tendency to not continue to develop relationship with the opposite sex that attracts their attention because they are worried about getting rejected due to having had leprosy; c) psychiatric problems characterized by low self-acceptance, anxiety and worry. The conclusion of this study is that the manifestations of leprosy have interrelated relationships between self-concept, relationships with the opposite sex, and social problems that have the potential to cause social dysfunction.